2007
DOI: 10.1104/pp.107.109587
|View full text |Cite
|
Sign up to set email alerts
|

Altered Profile of Secondary Metabolites in the Root Exudates of Arabidopsis ATP-Binding Cassette Transporter Mutants

Abstract: Following recent indirect evidence suggesting a role for ATP-binding cassette (ABC) transporters in root exudation of phytochemicals, we identified 25 ABC transporter genes highly expressed in the root cells most likely to be involved in secretion processes. Of these 25 genes, we also selected six full-length ABC transporters and a half-size transporter for in-depth molecular and biochemical analyses. We compared the exuded root phytochemical profiles of these seven ABC transporter mutants to those of the wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 56 publications
2
133
2
2
Order By: Relevance
“…[11][12][13][14][15] Sodium orthovanadate (Na 3 VO 4 ), a generic ABC-transport inhibitor, which blocks the release and/or uptake of root exudates, eliminated the increased lateral root number observed during KR studies with different accessions of A. thaliana. 19,20 These findings underscore the importance of such low-molecular weight secondary metabolites in mediating KR (Fig. 1).…”
Section: Introductionmentioning
confidence: 73%
“…[11][12][13][14][15] Sodium orthovanadate (Na 3 VO 4 ), a generic ABC-transport inhibitor, which blocks the release and/or uptake of root exudates, eliminated the increased lateral root number observed during KR studies with different accessions of A. thaliana. 19,20 These findings underscore the importance of such low-molecular weight secondary metabolites in mediating KR (Fig. 1).…”
Section: Introductionmentioning
confidence: 73%
“…In the latter case, the availability of genetic mutants impaired in biosynthesis and transport of specific rhizodeposit compounds has been crucial. For example, mutations in an Arabidopsis thaliana ABC-transporter gene, ABCG30 (resulting in increased exudation of phenolic acids and reduced exudation of sugars), caused significant changes in root microbial community structure as assayed by high-throughput sequencing of rRNA gene amplicons (Badri et al 2008(Badri et al , 2009). This study revealed the association of a number of potentially beneficial bacteria with abcg30 mutant roots.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recent reports indicate that the hormonal activation of ISR by ET/JA or SAR by SA showed no significant effect on the density and structure of the rhizosphere bacterial community (Doornbos et al, 2011). On the contrary, a recent report suggests that ATP-binding cassette transporters involved in root secretions may structure the rhizospheric microbiome (Badri et al, 2008). Carbon enrichment of the rhizosphere especially carboxylate excretion and acidification at the root surface might have a strong general impact on structuring rhizospheric microbial communities (Marschner et al, 2002).…”
mentioning
confidence: 98%